Articulate Storyline as a Modern Solution in Natural Science Learning in Elementary School - Rahmi, Sri Nur; Nurullah, Marno; Susilawati, Samsul (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
Articulate storyline-based learning has become an effective learning alternative in improving student learning outcomes, especially at the elementary school level. As the use of mobile devices increases among children, this approach provides an opportunity to create interactive and engaging learning experiences. This study aims to evaluate the influence of articulate storyline-based learning on the learning outcomes of elementary school students in Natural Sciences subjects. This study uses a quasi-experimental method with a control design involving 60 fourth grade elementary school students. Students were divided into two groups, namely the experimental group that used mobile learning applications and the control group that received conventional learning. Data was collected through pre-test and post-test tests to measure the improvement of learning outcomes and questionnaires to assess students’ responses to articulate storyline-based learning. Data analysis was carried out using statistical tests to determine significant differences between the two groups. The results showed that students who learned using mobile applications had a higher increase in learning outcomes compared to the control group. In addition, students in the experimental group also showed an increase in motivation and interest in learning, especially in the material delivered interactively. The conclusion of this study is that articulate storyline-based learning is influential in improving the learning outcomes of elementary school students and has the potential to be applied more widely at the basic education level.